1993
DOI: 10.2337/diacare.16.6.889
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Diabetic Retinopathy: The wide-angle retinal camera

Abstract: Fundus photographs taken by the 45 degrees camera through pharmacologically dilated pupils and read by trained readers perform as well as ophthalmologists for detecting diabetic retinopathy. Physician extenders can effectively perform the photography with minimal training but would require more training to perform adequate eye exams. In this older population, many patients did not obtain adequate nonpharmacological dilation for use of the 45 degrees camera.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
1
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(120 citation statements)
references
References 14 publications
7
110
1
2
Order By: Relevance
“…There is some evidence [18,19] that ophthalmologists screening for DR using direct ophthalmoscopy or slit lamp examination performed poorly (sensitivity 33 %) compared with internists using single 45°slides (sensitivity 54 %) and retinal specialists using two stereo 45°slides (sensitivity 81 %). Even in those countries where there are sufficient ophthalmologists, it is questionable whether screening for diabetic eye disease represents a cost efficient use of expensive specialist time if effective and more economical methods are available.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence [18,19] that ophthalmologists screening for DR using direct ophthalmoscopy or slit lamp examination performed poorly (sensitivity 33 %) compared with internists using single 45°slides (sensitivity 54 %) and retinal specialists using two stereo 45°slides (sensitivity 81 %). Even in those countries where there are sufficient ophthalmologists, it is questionable whether screening for diabetic eye disease represents a cost efficient use of expensive specialist time if effective and more economical methods are available.…”
Section: Discussionmentioning
confidence: 99%
“…The two methods that might possibly be considered as gold standard are seven-field stereoscopic photography and biomicroscopy carried out by a skilled ophthalmologist through dilated pupils. However, these methods have been compared in a number of studies [47][48][49][50] and do not show perfect agreement. 51 Hence, it is clear that one or both allow fairly frequent errors in detecting retinopathy.…”
Section: Human Grader Performance and Current Screeningmentioning
confidence: 99%
“…Tables 2.2.4 shows reported sensitivities and specificities of non-mydriatic camera studies. Some studies showed mydriatic retinal photography to be more sensitive than non-mydriatic photography (81% vs. 61% sensitivity) for detecting moderate NPDR, severe NPDR and PDR 24 . Mydriatic retinal photographs read by ophthalmic assistants, GPs and optometrists achieved sensitivities of 87%, 91% and 89%, respectively 22;366 , whereas non-mydriatic retinal photographs read by an ophthalmologist or trained grader generally achieved lower sensitivities, 56% and 60%, respectively 374 .…”
Section: Non-mydriatic (Undilated) Photographymentioning
confidence: 99%
“…In the absence of a dilated fundus examination by a trained examiner, use non-mydriatic (or mydriatic) photography with adequate sensitivity, specificity and low technical failure rate to detect presence of DR (Systematic review of diagnostic accuracy studies 20 and individual diagnostic accuracy studies [22][23][24][25][26] ).…”
mentioning
confidence: 99%